The impact of the crisis on the Greek «economic constitution» - Κατρούγκαλος Γιώργος Σ. Π. (The Greek Review of Social Research, 2011)
The article provides a critical overview of the constitutional aspects of the austerity measures introduced within the framework of the «Memorandum of Economic and Financial Policies» and the bailout of Greece by IMF, ECB and EU. The new rules which implement the related policy guidelines form a «parallel constitution», in the sense that they are contrary to many constitutional norms, including the fundamental principle of «Social State». The normative functions of the latter are described in the first part of the essay, whereas the second part deals more specifically with the unconstitutionality of the «Memorandum» policies.